Analisis Pengaruh Dana Pihak Ketiga (Dpk), Tingkat Sukubunga Kredit, Capital Adequacy Ratio (Car),Non Performing Loan (Npl) Dan Return On Assets (Roa) Terhadap Penyaluran Kredit Bank Pada Pt. Bank Tabungan Pensiunan Nasional (Btpn)Tbk Cabang Surakarta - Parmawati, Lidya Mukharomah, Zulfa Irawati, S.E., M.Si (2015)
The purpose of this research was to determine the extent to which the relationship of Third Party Funds (TPF) positive and significant effect toward the banking lending, and also the level of lending rates, Capital Adequacy Ratio (CAR), Non Performing Loans (NPL) and Return On Assets (ROA) negative and significant effect toward the banking lending PT BTPN, all Independent variablessignificant influential simultaneosly and the most dominant variable in lending. The data used in this study were obtained from Bank BTPN Limited Financial Report 2007-2014 period. Methods of data analysis used were multiple linear regression. Analysis of the regression performed after classical assumption test. These results indicate that the partial positive significant variableTPF, while the level of lending rates, CAR, NPL, ROA the partial no significant effect on lending, other that research result variable shows that TPF is the most variable the dominant in lending. Keywords: Banking Credit Distribution, TPF, CAR, NPL, and ROA